PERBEDAAN RERATA FAKTOR HEMOSTASIS PADA PEB, EKLAMPSIA DAN KEHAMILAN NORMAL - Yogi Syofyan; Joserizal Serudji; Hafni Bachtiar (Andalas Obstetrics And Gynecology Journal, 2019)
There will be multiple organs changes in preeclampsia and eclampsia. One of them is a change in hemostasis system which is platelet activation, extrinsic and intrinsic cascade reaction and increasing of fibrinolytic activation. This is a cross sectional study conducted at Obstetric and Gynecologic Departement of Medical Faculty of Andalas University/ M Djamil Central Hospital in Padang on July 2014 with the number of samples are 44 persons. Samples are divided into 3 groups: Severe preeclampsia, eclampsia, and normal pregnancy. Platelet, PT,APTT, and D-Dimer counting were conducted and statistic analyzed was done with Anova dan Post Hoc Bonferoni. The more severe pregnancy, the lower platelet count and PT, but the dif- ference is not statistically significant between three groups: severe preeclampsia, eclampsia, and normal pregnancy (p < 0,05). Mean of APTT and D-Dimer is statistically significant due to condition of pregnancy. Post Hoc Bonferroni analysis showed a significant difference of APTT mean in the eclampsia, severe pre-eclampsia, and normal pregnancy (p <0,05 ). D-Dimer Mean shows a significant difference between normal pregnancy, severe preeclampsia, and eclampsia (p <0,05).Keywords: Pregnancy condition, severe preeclampsia, eclampsia, normal pregnancy, platelet, PT, APTT, and D-Dimer